Oncological and Functional Outcomes in Joint-sparing Resections of the Proximal Femur for Malignant Primary Bone Tumors. Issue 8 (7th September 2021) - Ramkumar, Dipak B.; Kelly, Sean P.; Ramkumar, Niveditta; Ercolano, Lisa B.; Lozano-Calderon, Santiago; Gebhardt, Mark C.; Anderson, Megan E.
Abstract : Background: Joint-sparing resections (JSR) of the proximal femur allow for preservation of the proximal femoral growth plate and native hip joint, but whether this offers fewer complications or better function and longevity of the reconstruction remains unknown. In this study, we compared the functional outcomes of pediatric patients with bone sarcomas undergoing JSR of the proximal femur with intercalary allograft (ICA) reconstruction to those undergoing proximal femoral resections (PFR) with allograft-prosthetic composite (APC) reconstructions. Methods: We retrospectively reviewed all patients undergoing JSR with ICA reconstruction and PFR with APC reconstructions between 1995 and 2013 at a tertiary pediatric referral center. Primary outcomes included major and minor complications and secondary outcomes included the need for a secondary procedure, presence of local or distant relapse, survival status, and the presence of pain and ambulatory status (limp, assistive device, highest level of function). We assessed differences in outcomes using the Fisher exact and Wilcoxon rank-sum tests. Results: Eight patients underwent a JSR and ICA reconstruction, while 7 patients underwent a PFR with APC reconstruction. Median patient follow-up was 60.4 months (interquartile range: 36.8 to 112.9) Patients undergoing JSR and ICA reconstruction were younger than patients undergoing PFR with APC reconstruction (7.7 vs. 11.7 y, P =0.043); however, we found no other statistically significant differences in patient demographics. There were no statistically significant differences in primary or secondary outcomes between the study groups; however, patients who underwent JSR with ICA had more major complications (62.5% vs. 42.9%, P =0.29) and a lower rate of minor complications (25% vs. 28.6%, P =0.22). Conclusion: Treatment of proximal femoral bone sarcomas in pediatric and adolescent patients remains a challenging enterprise. JSR with ICA reconstruction in the proximal femur, when feasible, may provide a similar function and risk of intermediate-term major and minor complications when compared with PFR with APC reconstruction. Further long-term studies are required to determine the impact of the native femoral head retention with respect to revision rates. Level of Evidence: Level III, retrospective comparative study.